Globalfocusing: From Domestic Conglomerates to Global Specialists* - Meyer, Klaus E. (Journal of Management Studies, 2006)
abstract Globalization is changing the competitive terrain on which companies develop their corporate strategy. On the global stage, key competitive advantages are gained through internationally fungible resources. Consequently, diversified conglomerates are converting to global specialists in narrower niche markets and competing with a small number of multinational enterprises operating worldwide. Their internationalization and their reduction of product diversification are opposite sides of the same coin: globalfocusing. I extend Penrosian resource‐based theory to analyse this change process, notably by distinguishing country and industry specificity of firms' core competences, and by integrating divestment as part of firm growth processes. Globalfocusing is driven by shifts in the relative importance of country‐specific and industry‐specific resources and capabilities due to changes in the internal and external environment, notably the globalization of markets and supply chains. The argument is developed using case studies of restructuring of two Danish manufacturing enterprises. On this basis, I analyse the forces driving globalfocusing processes and suggest propositions for empirical testing.